A Review Paper on: Power Grid Associated with Web using Non-Conventional Energy Source - Rasane, Kalpesh; Baviskar, Prakash (International Journal of Computer Sciences and Engineering, 2025)
This paper proposes a household power unit which is able to automatic switching and will communicate through Ethernet/Wi-Fi so utilization of the Non-conventional energy sources like solar energy will become more reliable. Further it will have made ready to end-user through electrical setup. The ARDUINO MEGA processor is preferred to work as an Embedded Device. The program loaded on this device will be work as Real time operating system. It is necessary to process, control and communication. Other services are provided on the top of embedded device. It includes communication with server about the real-time information on energy meters at customer`s location. Energy source selection, power-up the connection and disconnection are some of the services that are provided through the online web portal. The web browser available at subscriber`s end, can act as an interface to these services provided. Greater integration of renewable energy generation may be achieved by facilitating battery energy storage systems like integrating remote access to manage the set up like Ethernet, Web communication etc. The smart energy management of the resources is very important aspect. It allows collection of energy from multiple sources. In case of commercial and large scale implementation, the generated power at distribution level can be directly fed to the utility distribution network. In this paper, the smart energy management system is used where the battery monitoring system works alternately. ARDUINO MEGA 7 microcontroller is used to regulate the actual operating function as a core part of the setup. It is ideally appropriate for residential premises along with commercial applications.